Synthesis, α-glucosidase and α-amylase inhibitory activities, acute toxicity and molecular docking studies of thiazolidine-2, 4-diones derivatives. Issue 18 (19th October 2022) - Fettach, Saad; Thari, Fatima Zahra; Hafidi, Zakaria; Tachallait, Hamza; Karrouchi, Khalid; El achouri, Mohammed; Cherrah, Yahia; Sefrioui, Hassan; Bougrin, Khalid; Faouzi, My El Abbes
Abstract: In the present study, a series of thiazolidine-2, 4-diones derivatives (3a–3e ) and (4a–4e ) were synthesized and characterized by 1 H NMR, 13 C NMR and ESI-MS spectrometry. All compounds were screened for their α-glucosidase and α-amylase inhibitory activities. In vitro biological investigations revealed that most of compounds were active against α-glucosidase with IC50 values in the range of 43.85 ± 1.06 to 380.10 ± 1.02 µM, and α-amylase with IC50 in the range of 18.19 ± 0.11 to 208.10 ± 1.80 µM. Some of the tested compounds were found to be more potent inhibitors than the clinical drug Acarbose (IC50glucosidase = 97.12 ± 0.35 µM and IC50amylase = 2.97 ± 0.004 μM). The lead compounds were evaluated for their acute toxicity on Swiss mice and found to be completely non-toxic with LD > 2000 mg/kg BW. Furthermore, the Structure–activity relationship (SAR) and the binding interactions of all compounds with the active site of α-glucosidase and α-amylase were confirmed through molecular docking and stabilizing energy calculations. This study has identified the inhibitory potential a new class of synthesized thiazolidine-2, 4-diones in controlling both hyperglycemia and type 2 diabetes mellitus. Furthermore, the theoretical binding mode of the target molecules was evaluated by molecular docking studies against the 3D Crystal Structure of human pancreatic α-amylase (PDB ID: 1B2Y) and α-glucosidase (PDB ID: 3W37) Communicated by Ramaswamy H. Sarma